Răspuns :
Răspuns:
x-3y+3=0 |•3
-3x+y-3=0 |•(-1)
3x-9y+9=0
3x-y+3=0
----------------(+)
\ 10y+12=0
10y=-12
y=-12/10= -6/5
Folosim metoda substituției
——————
{x=3y-3
-3x+y=0
-> Înlocuim valoarea lui X în ecuația:
-3(3y-3)+y-3=0
y=3/4
->Înlocuim valoarea lui y
x=3 • 3/4 -3
x=- 3/4
—> { - 3/4-3•/4+3=0
-3•(3/4)+3/4-3=0
-> { 0=0
0=0
—>Soluție= {-3/4 ; 3/4 }
——————————
Explicație: 3/4 =3 supra 4
• = ori
——————
{x=3y-3
-3x+y=0
-> Înlocuim valoarea lui X în ecuația:
-3(3y-3)+y-3=0
y=3/4
->Înlocuim valoarea lui y
x=3 • 3/4 -3
x=- 3/4
—> { - 3/4-3•/4+3=0
-3•(3/4)+3/4-3=0
-> { 0=0
0=0
—>Soluție= {-3/4 ; 3/4 }
——————————
Explicație: 3/4 =3 supra 4
• = ori